Perkembangan Kajian Al Qur’an di Maroko Studi Pemikiran Ibrahim Al Wafi Dalam Karya Dirasah Qur’aniyah Bil Maghrib, Fil Qur’ani Ar Rabi Ashara Hijri - Faozan, Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Ibrahim bin Ahmed Al-Wafi, through the book entitled, Perceived the Qur'an in the Maghreb, Qur'anic Ar Rabi Ashara Hijri, encouraged the study of the ultimate Qur'an to us all. Departing from the intellectual restlessness of an Ibrahmi Al Wafi this, prompted him to answer various questions while conducting this research which has been booked. In this monumental work, Ibrahim Al Wafi divides the contents of his book into three chapters. Every chapter he reads in depth. Through this work, he has contributed to the thought of the latest Qur'anic study. Especially related to, how the Muslim citizens of Morocco in dialectic with the great civilizations in the early 14th century AH.